Education, Customs, and Laws as Foundations for the Promotion of Civic Virtues in the Protagoras and the Republic - Motta, Guilherme Domingues da (Revista Archai, 2025)
In Plato’s Protagoras to defend his view accor-ding to which virtue can be taught, Protagoras offers a brief description of the traditional Greek education in his time and assigns to it, to the customs and to laws the power to promote the achievement of the fundamental civic virtues, although stressing the role of coercion in that process. A comparison with the model of education proposed in the Republic and which aims at promoting the same virtues show a remarkable similarity between the two conceptions. However, there are some fundamental differences between the two views. In the first dialogue mentioned, the sophist seems much more optimistic than the Socrates of the second dialogue about the possibility of promoting virtue. What seems clear is that according to this Socrates, a very profound intervention is needed in the education and customs before one can expect men to acquire and maintain the fundamental civic virtues. This intervention seems based on a deep knowledge of the human soul and of the forces at play in it. It also seems founded on an understanding of how to intervene in order to promote the right ordering of the soul that will make the virtues possible.